Screen enemies of the American way political paranoia about Nazis, Communists, saboteurs, terrorists and body snatching aliens in film and television - Sherman, Fraser A. (McFarland & Company, Inc., Publishers, 2011)
"American films, like America itself, have long been fascinated by the threat of outsiders posing as citizens to destroy the American way of life. This book tracks real-world fears appearing in the movies and shows how these issues, and others, played out on screen."--Provided by publisher.